Speeches June 1987 - May 1988 - Sandiford, L. Erskine (Government Information Service St. MichaelBB)
Presents a number of speeches dealing with topics such as foreign policy; regional integration; industrial relations, the Barbadian economy; trade relations; and the security exchange.